RP-HPLC-based phytochemical screening of different polyphenolic compounds from floral extract of four species of Saraca L. (Leguminosae) - Sujit Sil; Kalyan K. De; Asok Ghosh (SpringerOpen, 2022)
Abstract Background Saraca L. is one of the treasures throve of medicinally important plants in Indian subcontinent with its four species among which two are naturally distributed. It is one of the important resources of highly active phytochemicals due to which it proclaims a legendary position from ancient medicinal practices to modern ages. The crude extracts of flowers of four species were prepared using Soxhlet apparatus in petroleum benzene, ethyl acetate and 90% methanol sequentially. RP-HPLC (reverse-phase high-performance liquid chromatography)-based analysis of the presence of different phytochemicals using 15 different polyphenolic phytochemical standards was done to assess and quantify different phytochemicals. Results RP-HPLC-based evaluation revealed the presence different polyphenolic compounds like catechins, chlorogenic acid, vanillic acid, caffeic acid, gallic acid, t-cinnamic acid, anthrol, p-coumaric acid, biochanin A, etc., in a considerable amount which is very crucial for the phytomedicinal field. The correlations of the presence of known phytochemicals give a basis of phytochemical correlation among the four species. The RP-HPLC chromatographic data were applied to develop the complete phytochemical coding according to the complete set of chemicals found among the species to evaluate phytochemical correlation among them in a different way. This application also produces strong evidence of distinguishing features of S. indica and S. asoca that were considered as same species by some traditional taxonomy. Conclusion Extracts of S. thaipingensis contain highest amount of polyphenolic compounds, and the lowest amount was found in S. declinata. The phytochemical relations among S. asoca and S. declinata are high, and S. indica also has close relations with them, but S. thaipingensis has distinct divergence.